Enhanced electrocatalytic property of Pt/C electrode with double catalyst layers for PEMFC. (20th September 2019) - Van Dao, Dung; Adilbish, Ganpurev; Lee, In-Hwan; Yu, Yeon-Tae
Abstract: The objective of this study was to fabricate an efficient structural catalyst electrode of Pt/C consisting of double catalyst layers (DCL) with catalyst-ink spray and electrophoresis deposition (EPD) methods. The prepared Pt/C DCL electrode with Pt-dispersed and Pt-concentrated catalyst layers demonstrated better electrochemical properties than individual Pt/C single catalyst layer (SCL) electrodes. An S1 E1 DCL electrode with Pt loading weight ratio of 1:1 between the Pt-dispersed and Pt-concentrated layers exhibited a higher electrochemical surface area (ECSA, 57.2 m 2 /gPt ) and lower internal resistance (20 Ω) than an individual Pt-dispersed SCL electrode prepared with only the spray method (S1 E0, 31.9 m 2 /gPt and 132 Ω) and an individual Pt-concentrated SCL electrode prepared with only the EPD method (S0 E1, 34.1 m 2 /gPt and 120 Ω). The S1 E1 DCL electrode exhibited 2.1 and 1.7 times higher mass activity for methanol oxidation reaction (MOR) than S1 E0 and S0 E1 SCL electrodes, respectively (1, 230 mA/mgPt for S1 E1 vs. 595 mA/mgPt for S1 E0 and 715 mA/mgPt for S0 E1 ). In addition, the S1 E1 DCL electrode demonstrated high MOR durability after 1, 000 sequential cycles while losing 30% activity. Meanwhile, S0 E1 and S1 E0 SCL electrodes rapidly lost 52% and 55% activity, respectively. These improved electrochemical performances of DCL electrode were owing to the advantages of separating Pt catalysts into two layers, which provides more Pt catalytic active sites to the electrolyte than those in SCL electrodes. Our observation may aid in minimizing the usage amount of Pt catalysts ( 0.16 mgPt /cm 2 ) compared to those in present commercial Pt/C composites ( 0.3 mgPt /cm 2 ) as well as maximize efficient Pt utilization. More importantly, with regard to proton exchange membrane fuel cell (PEMFC) activity as a crucial in-situ characterization of a catalyst, a membrane electrode assembly (MEA) containing S1 E1 as the anode electrode could generate mass maximum power density of 3.84 W/mgPt, 3.6 times higher than the present commercial one (1.07 W/mgPt ). Graphical abstract: Image 1 Highlights: Pt/C electrodes with double catalyst layers (DCL) are fabricated. Pt/C DCL shows good HOR and MOR activity compared to Pt/C EPD and spray electrodes. Pt/C DCL provides more Pt active sites to electrolyte to maximize Pt utilization. This design can be effective for PEMFC applications.